2016
DOI: 10.1002/2015jf003607
|View full text |Cite
|
Sign up to set email alerts
|

Landscape response to late Pleistocene climate change in NW Argentina: Sediment flux modulated by basin geometry and connectivity

Abstract: Fluvial fill terraces preserve sedimentary archives of landscape responses to climate change, typically over millennial timescales. In the Humahuaca Basin of NW Argentina (Eastern Cordillera, southern Central Andes), our 29 new optically stimulated luminescence ages of late Pleistocene fill terrace sediments demonstrate that the timing of past river aggradation occurred over different intervals on the western and eastern sides of the valley, despite their similar bedrock lithology, mean slopes, and precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 127 publications
1
79
2
Order By: Relevance
“…Climate change in the tropics and subtropics associated with rapid changes in erosion, soil thickness, and vegetation cover is the focus of many recent research efforts to better understand the impact of environmental change on landscapes (e.g., Pelletier et al, 2015;Schildgen et al, 2016). Paleo-environmental changes recorded by proxy indicators in marine and terrestrial sediments may serve as powerful proxies of landscape response to both present-day climate variability and future climate change (e.g., deMenocal et al, 2000;Shanahan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change in the tropics and subtropics associated with rapid changes in erosion, soil thickness, and vegetation cover is the focus of many recent research efforts to better understand the impact of environmental change on landscapes (e.g., Pelletier et al, 2015;Schildgen et al, 2016). Paleo-environmental changes recorded by proxy indicators in marine and terrestrial sediments may serve as powerful proxies of landscape response to both present-day climate variability and future climate change (e.g., deMenocal et al, 2000;Shanahan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the tributary catchments in the arid sector north of Volcán host thick fluvial fill terraces and fans (abandoned surfaces standing up to 150 m above the modern river level), while catchments in the subhumid sector south of the Del Medio fan record only limited deposition in the vicinity of the confluence with the Rio Grande. Landslides are known to occur throughout the Humahuaca Basin, both north and south of the fan, with more frequent, low‐volume landsliding events observed in wetter regions today [ Paolini et al ., ] and more frequent landsliding proposed to have occurred during wetter periods in the past across the region [ Trauth et al ., ; Bookhagen et al ., ; Haselton et al ., ; Schildgen et al ., ].…”
Section: Study Sitementioning
confidence: 99%
“…To characterize the processes and local conditions that have led to aggradation in the Del Medio catchment, we combine field observations with measurements of in situ produced cosmogenic 10 Be in sand and pebbles. Differences in cosmogenic nuclide concentrations between sand and pebbles are thought to be related to the dominant erosional mechanisms [ Belmont et al ., ; Aguilar et al ., ; Codilean et al ., , ; Carretier et al ., , and references therein; Schildgen et al ., ], with landslides releasing larger grains with lower 10 Be concentrations. In an effort to establish a chronology of the most recent activity on the fan, we determine exposure ages by measuring 10 Be concentrations of boulder surfaces and depth profiles.…”
Section: Introductionmentioning
confidence: 99%
“…1) to identify and measure areas of dh in gravel-bed channels specifically and then across the landscape. Here, steep gradients in elevation (~1-4 km), rainfall (~0.1-1 m/yr), and vegetation (sub-tropical forests and croplands to arid, succulent-covered slopes) cause high rates of mass transfer (Bookhagen and Strecker, 2012;Savi et al, 2016;Schildgen et al, 2016), further influenced by climate change (Castino et al, 2016a(Castino et al, , b, 2017 and anthropogenic modification (gravel mining and weirs). To conclude, we discuss caveats driven by remaining uncertainties prevalent in spaceborne DEMs collected over complex topography.…”
mentioning
confidence: 99%
“…8), we see that these automated measurements can be correlated with additional sources. For Río Grande, the steep knickpoint at the Del Medio fan Schildgen et al, 2016) causes a major zone of incision immediately followed by aggradation where the material is deposited. Fieldwork has indicated that 15 some of this incision is man-made, caused by attempted removal of aggrading material coming from the productive (e.g., debris flows cf.…”
mentioning
confidence: 99%